ETHICS AND PUBLIC TRUST IN AI GOVERNANCE: A LITERATURE REVIEW - Norainie Ahmad; Muhammad Anshari; Mahani Hamdan; Emil Ali, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
As AI systems become ubiquitous, policymakers and regulators must establish effective governance frameworks that fortify ethical values. Such a model should be value-driven, principle-based, and maintain ethical integrity and public trust. Challenges include generative AI’s potential to exacerbate disinformation and other risks. This paper addresses integrating values into AI governance to foster ethical integrity and support innovation. Bibliometric analysis and case studies identify key value tensions and tradeoffs in AI regulation. We propose a governance framework that harmonizes values like transparency, accountability, and inclusivity with AI development. Collaborative governance and unlikely stakeholder coalitions can foster an innovation ecosystem prioritizing ethical practices. The findings guide policy and industry actors navigating AI regulation to align development with social and ethical values.